(untitled) (PerCursos, 2023)
This study aims to analyze the concept of territory as an indispensable knowledge for the resistance of rural peoples and traditional communities. Its epistemic basis is frontier thinking, and bibliographical and documentary research and interviews are its methodological bases. It analyzes how the devaluation of the territorial ties of other peoples conceal their importance, based on ethnic and racial differences, in the sense of interference in the production of knowledge. It highlights the importance of implanting the colonizer’s dominant territoriality, anchored in the subjectivity of land as a commodity, for the coloniality of nature. It seeks to elucidate the correlation between land management and coloniality and its interrelation with the mythical categories that revitalize the complex colonization of the imaginary of inferiorized peoples for their control. It analyzes concepts and examples that have anchored resistance in the opposite direction of coloniality, towards decoloniality or counter-colonization. It highlights the importance of territory as an epistemic locus and points to the conceptual importance of territory as a basis for the resistance of diverse peoples and populations from the countryside in Latin America.